Low-voltage all-nmos four-quadrant current multiplier - Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2018)
This paper presents a low-voltage four-quadrant current-mode multiplier circuit using all-NMOS technique. The circuit is constructed using current-squaring function circuits and simple current mirrors, where all small-signal currents pass through only NMOS transistors. The proposed current multiplier is simple and suitable for low-voltage, low-power operation. The circuit performances were demonstrated by PSPICE simulations with TSMC 0.35-μm CMOS process. To show the basic function of the proposed circuit, the frequency doubling and amplitude modulating circuits have been performed and simulated.
Keywords: Analog multiplier; Current-mode circuits; Low-voltage circuits; MOS analog circuits; Squarer